PENGARUH SOSIAL – EKONOMI DARI SENTRA INDUSTRI KECIL (STUDI KASUS PADA CV. MITRA KENCANA MAKMUR KOTA JAMBI) - Edison Edison (J-MAS (Jurnal Manajemen dan Sains), 2017)
An analysis of a small industry is a wide variety and refers to developing and empowering; therefore, in a long term, it can be autonomous in a strict competition. The study aims to examine a small industry performance of chips in Kota Jambi. The study is useful for describing the characteristics of industry specifically. The findings of the study indicate that UKM (middle-small sized industry) in a variety of forms has different characteristics. However, there are a number of serious problems for sustainability. Some problems are a license, location and capital since a majority of UKM is not bankable, a lack of human resources including regeneration and succession for sustainability, dualistic leadership as owner as well as manager, serious management problem – incredible accounting, pay standard, raw-material assurance, additional product, marketing aspect and waste of production. A further research needs to design all problems referring to the findings of the UKM cases in industry center for chips. Although the generalization of the findings is not broad, it shows a classical problem of UKM to need analyzing more intensively for answering the problem. For a further research, thus, it is necessary to include all of the parties to find a solution for the continuity of UKM that can positively contribute to labor market recruitment and micro and macro economy improvement. However, the study is limited to the case so that the generalization can not be reached. The conclusion, but, can concretely describe a variety of problems.Keywords: UKM, industral center, empowering